(untitled) (Repertorio Científico, 2020)
The results of an educational experience are presented in the attention of blind university students who are preparing to be teachers in I and II Cycles of the Costa Rican Basic General Education. The information corresponds to the case of a student who was studying Mathematics I for I and II Cycles, in which she must develop a mini-class. The student is offered a didactic strategy in which to use concrete material on the subject of fractions, but she changes the plans of the researchers and challenges them to make adjustments to address a proposal on the subject of basic operations.